Molecular mechanisms and physiological functions of mitophagy - Onishi, Mashun; Yamano, Koji; Sato, Miyuki; Matsuda, Noriyuki; Okamoto, Koji (The EMBO journal, 2021)
Degradation of mitochondria via a selective form of autophagy, named mitophagy, is a fundamental mechanism conserved from yeast to humans that regulates mitochondrial quality and quantity control. Mitophagy is promoted via specific mitochondrial outer membrane receptors, or ubiquitin molecules conjugated to proteins on the mitochondrial surface leading to the formation of autophagosomes surrounding mitochondria. Mitophagy‐mediated elimination of mitochondria plays an important role in many processes including early embryonic development, cell differentiation, inflammation, and apoptosis. Recent advances in analyzing mitophagy in vivo also reveal high rates of steady‐state mitochondrial turnover in diverse cell types, highlighting the intracellular housekeeping role of mitophagy. Defects in mitophagy are associated with various pathological conditions such as neurodegeneration, heart failure, cancer, and aging, further underscoring the biological relevance. Here, we review our current molecular understanding of mitophagy, and its physiological implications, and discuss how multiple mitophagy pathways coordinately modulate mitochondrial fitness and populations. Graphical Abstract This review describes the conserved pathways for mitochondrial degradation via selective autophagy across species, and how multiple mitophagy pathways cooperate to modulate mitochondrial fitness and number in normal or disease physiology.